GEOCHEMICAL CHARACTERISTICS OF PEAT ACCUMULATION PROCESSES IN THE ALTAI PIEDMONT - Matukhina V.G.; Popova M.V. (My University, 2001)
The geochemical characteristics of peats and regularities in the distribution of mineral components have been studied in peat deposits in the Altai piedmont. These regularities depend on a number of factors including the closeness of the studied deposits to source areas, the petrographic compositions of rocks in these areas, the geomorphologic position of drainage systems and peat deposits, the amount of a mineral substance input, and the intensity of postsedimentation processes. For the first time, we have traced regularities of gold transformation in peats and revealed a trend of gold accumulation caused by diagenetic alterations. It was shown that element concentrations in peats exceeding clarkes could be used as a criterion for prospecting ore accumulations in source areas. The use of systems analysis for establishing the genetic nature of minerals allows us to trace mineral-formation processes at various stages of sedimentation and diagenesis and assess the possibility of discovering ore formation products.